Illegal gambling on sports: a mediational model of general strain theory - Kabiri, Saeed (Criminal justice studies, 2020)
Studies involving illegal gambling in sports are important, though most lack a theoretical framework. The current study examines illegal gambling in sports using a mediational model of General Strain Theory. This features a survey of three-hundred and ninety-two (n = 392) gamblers in Rasht, Iran. Results indicate that participants who experience subjective financial strain also experience negative emotions, which leads to a greater likelihood of illegal gambling. The concepts of financial strain (low SES) and control deficit emerged as significant in the development of gambling behaviors. The results suggests that gambling on sports behavior is learned in a similarly to pro-social behaviors, and that desistance requires an consideration of the learning process.